An experimental evaluation of adaptogenic potential of standardized epipremnum aureum leaf extract - Sreemoy Kanti Das; Pinaki Sengupta; Mohd Shahimi Mustapha; Md Moklesur Rahman Sarker (Wolters Kluwer Medknow Publications, 2017)
Background: Stress is a normal part of everyday life but chronic stress can lead to a variety of stress-related illnesses including hypertension, anxiety, and depression. In the present investigation, standardized leaf extract of Epipremnumaureum was evaluated for its anti-stress potential. Materials and Methods: For the evaluation of anti-stress activity, groups of mice (n = 6) were subjected to forced swim stress and anoxic stress tolerance test in mice 1h after daily treatment of E.aureumextract. Diazepam (5 mg/kg) was taken as a reference standard. Urinary vanillylmandelic acid (VMA) and ascorbic acid were selected as noninvasive biomarkers to assess the anti-stress activity and plasma cortisol, blood ascorbic acid, and weight of adrenal were measured. The 24 h urinary excretion of VMA and ascorbic acid were determined by spectrophotometric methods in all groups under normal and stressed conditions. The hematological parameters (neutrophils, lymphocytes, and eosinophils) were also determined. Results: Administration of E.aureumat doses of 400 and 600 mg/kg wasfound to be effective in inhibiting the stress induced urinary biochemical changes in a dose-dependent manner. Treatment with E. aureum extract prevents the rise in blood ascorbic acid and plasma cortisol. Moreover, the extract prevented the increase in weight of adrenal gland also significantly increased the anoxia stress tolerance time. Dose-dependent significant reduction in white blood cell count was observed in anoxic stress tolerance test as compared to stressed group. Conclusion: Hence, the present study provides scientific support for the positiveadaptogenic effect of E. aureum extract.